Prostate cancer survivorship priorities for men and their partners: Delphi consensus from a nurse specialist cohort. Issue 1 (27th November 2019) - Ralph, Nicholas; Green, Anna; Sara, Sally; McDonald, Suzanne; Norris, Philip; Terry, Victoria; Dunn, Jeffrey C.; Chambers, Suzanne K.
Abstract: Aims & objectives: To describe the prostate cancer survivorship experience and priorities from the perspective of prostate cancer specialist nurses. Background: Specialist nurses are providing long‐term survivorship care to men and their partners however, few prostate cancer survivorship interventions are effective and priorities for nurse‐led survivorship care are poorly understood. Design: A three‐round modified Delphi approach. Methods: The study was conducted between 1 December 2018 and 28 February 2019 to develop a consensus view from an expert nurse cohort (43 prostate cancer specialist nurses: 90% response). First, participants described men's prostate cancer survivorship experience and priorities for improving care for men and partners. In subsequent rounds, participants identified key descriptors of the survivorship experience; rated priorities for importance and feasibility; and identified a top priority action for men and for partners. Thematic analysis and descriptive statistics were applied. Guidelines for Reporting Reliability and Agreement Studies informed the conduct of the study. Results: Prostate cancer specialist nurses characterised the prostate cancer survivorship experience of men as under‐resourced, disjointed and distressing. In all, 11 survivorship priorities for men and three for partners were identified within five broad areas: capacity building; care coordination; physical and psychosocial care; community awareness and early detection; and palliative care. However, feasibility for individual items was frequently described as low. Conclusion: Internationally, prostate cancer survivorship care for men and their partners requires urgent action to meet future need and address gaps in capacity and care coordination. Low feasibility of survivorship priorities may reflect translational challenges related to capacity. Prostate cancer survivorship care guidelines connected to practice priorities are urgently needed. Relevance to clinical practice: These findings address key gaps in the evidence for developing national nurse‐led prostate cancer survivorship priorities. These priorities can be used to inform survivorship guidelines including nursing care for men with prostate cancer and their partners.